PENGARUH AGENCY COST TERHADAP KINERJA PERUSAHAAN DENGAN CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI - Ria, Ria Rezki Amalia; yana, Yana firana; Edy, Edy Fitriawan Syahadat (AkMen JURNAL ILMIAH, 2024)
Agency problem (agency conflict) that occur in the company raises agency cost that could affect the firm performance. The study aimed to test the effect of (1) agency cost on company’s performance, (2) moderation of managerial ownership on the relationship between agency cost and company’s performance, (3) moderation of institutional ownership on the relationship between agency cost and company’s performance, (4) proporation moderation of independent board of commissioners on the relationship between agency cost and company’s performance, and (5) moderation of audit committee on the relationship between agency cost and company’s performance. The samples of the study were 4 state owned enterprises (BUMN) in the fields of mining, strategic industry, energy, and telecommunication listed at the Indonesia Stock Exchange. The samples were selected by using purposive sampling technique. The data were annual report of the companies of 2010-2014 period obtained from the Indonesian Capital Exchange (IDX). The analysis used in the study was multiple linear regression. The result of the study indicate that (1) the agency cost had a negative significant effect on the company’s performance, (2) the interaction between agency cost and managerial ownership had a positive significant effect on the company’s performance, (3) the interaction between agency cost and institutional ownership had a positive significant effect on the company’s performance, (4) the interaction between agency cost and proportion of independent board of commissioners had a positive significant effect on the company’s performance, and (5) the interaction between agency cost and audit commitee had a positive significant effect on the company’s performance. Keywords: agency cost, company’s performance, corporate governance.